Organisational and professional commitments: the influence in nurses´organizational citizenship behaviours - Duarte, Márcia Brito (2015)
The way an employee behaves in his work can be influenced by the organisational and professional commitment. Nurses are professionals who are guided by organisational and professional goals and values. Among nurses, professional commitment may be an important antecedent of organisational citizenship behaviours. The study shows how organisational and professional commitment is related with nurses’ organisational citizenship behaviours. Data from a sample of 420 nurses working in two hospitals --- the Hospital of St. Marcos, Braga and the Hospital Centre of Alto Ave, Guimarães and Fafe units were collected. The main findings are as follows: (a) organisational commitment and professional commitment contribute to the explanation of nurses’ organisational citizenship behaviours, (b) affective organisational commitment, continuance organisational commitment --- personal sacrifice, affective professional commitment and continuance professional commitment explain 28.6% of variance of organisational citizenship behaviours. © 2013 Instituto Politécnico do Cávado e do Ave (IPCA). Published by Elsevier España, S.L.U. All rights reserved.